Justification work: The homeless workers' movement and the pragmatic sociology of dissent in Brazil's crisis. Issue 1 (3rd April 2018) - Albert, Victor; Davidenko, Maria
ABSTRACT: In the late 2000s, a number of analysts were optimistic about Brazil's future. Their expectant analyses did not bear out, however, as a political and economic crisis developed just as Brazil was gearing up to host two mega-events, the World Cup in 2014 and the Olympic Games in 2016. This paper has two aims. The first is to deepen our understanding of the crisis through examining one of the foremost civil society actors to emerge in this period: the Landless Workers' Movement (Movimento de Trabalhadores Sem-Teto, MTST). The second is to use this case to consider the potential for the sociology of critical capacity - a field of theory that emerged out of the Political and Moral Sociology Research Group in Paris in the 1980s - to contribute to theorising the 'justification work' of social movements.